Replacing corn and soybean meal with a combination of wheat bran and urea on performance of grazing suckling beef calves - Aghata Elins Moreira da Silva; Deilen Paff Sotelo Moreno; Camila de Paula; Naycker Patricia Veríssimo dos Santos; Danilo Henrique Souza da Silva; Gutierrez José de Freitas Assis; Arturo Macias Franco; Edenio Detmann; Luciana Navajas Rennó; Mário Fonseca Paulino (Semina: Ciências Agrárias)
The objective of this study was to evaluate the effects of replacing corn and soybean meal with a combination of wheat bran and urea in a protein-energy supplement on productive, nutritional, and metabolic characteristics of grazing suckling beef calves. Fifty-two Nellore calves (87±4.95 days of age; 111.3±5.98 kg of initial body weight [BW]) were allocated in a completely randomized design with 4 treatments and 13 replicates. The 140-d trial evaluated treatments consisting of progressive replacing corn and soybean meal with wheat bran and urea (0, 50, and 100%) and a control group receiving only mineral mixture. Supplements were formulated to contain 20% of crude protein (CP), provided in the amount of 7 g kg-1 BW. Dry matter, organic matter, CP, total digestible nutrients and digested organic matter (DOM) intake were higher for animals receiving supplementation than those without supplementation (P<0.01). Among the animals that receiving protein-energy supplementation, the non-fiber carbohydrates (NFC) intake displayed a linear decreasing effect, while for the CP-to-DOM ratio a linear increasing effect was observed (P=0.006). The NFC digestibility was higher for the animals that received supplement (P=0.035), and among these animals a linear decreasing response for DOM digestibility was observed (P=0.046). Additionally, the neutral detergent fiber digestibility of these animals showed a quadratic response (P=0.023). Overall, the supplemented animals exhibiting a higher BW at weaning (P=0.047). However, no differences were observed in the performance among the supplemented calves (P>0.05). Concentrations of insulin-like growth factor-1 and serum urea nitrogen were higher for animals receiving supplementation (P<0.041).  In conclusion, replacing corn and soybean meal with a combination of wheat bran and urea as a source of protein-energy supplement at 7 g kg-1 BW is recommended for suckling beef calves on tropical pastures.